Cognitive variability - Badham, Jennifer (Department of Psychology, 2023)
Throughout psychological literature there are many, and ever increasing, references to a variable, usually presumed to be related to certain personality phenomena, which has~ been described as flexibility, fluidity, rigidity, perseveration, variability, and other similar terms. Generally, all these terms have refenced to the idea that the behaviour of people in different situations or of different people in the same situation··, varies along a continuum marked at one end by extreme limitation of reaction and at the other by extreme freedom of response. The use of this vague terminology and the fact that general concepts and definitions have been left far from clear, has rendered any approach to the topic extremely difficult, and I can echo with feeling the words of Chown (1959) when she said 11FeVJ major topics in contemporary psychology offer more promise than this one or present such a quagmire of confusion to the unwary investigator"! Probably the most satisfactory means of gaining a clear VieVJ of the field is with an historical perspective; I propose therefore to adopt this approach and to deal with the relevant literature under the general heading of - "Theories and types of rigidity fle:xibility11 It will be seen that it has been considered best to make a three-fold division of the literature - namely into that concerned with (l) 11Perseveration11 and "rigidity", (2) the rigid personality, and (3) Variability as such, although of necessity a certain amount of overlap does